PENGARUH PROGRAM DISKON DAN SOCIAL PROOF TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE DI SHOPEE : (STUDI KASUS KONSUMEN DI KOTA SUKABUMI) - Mia, Nuraini; Maulana, Rizky (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to determine the Influence of Discount Programs and Social Proof on Purchase Decisions for Skincare Products by Shopee consumers in Sukabumi City. The method used in this study is the Associative Quantitative research method. Because the population in this study is unknown, the Chocran formula is used to determine the sample in this study with a total of 97 respondents. The technique used in this study is non-probability sampling with a sample determination technique, namely Purposive sampling. Based on the results of the t-test (partial) shows that the Discount Program variable has a positive and significant effect on Purchase Decisions. Where the t count of the discount program variable is 4.716> 1.985 (t table) with a significant value of 0.000 <0.05 (significance level). And the Social Proof variable has a positive and significant effect on Purchase Decisions. Where the t count of the social proof variable is 5.233 > 1.985 (t table) with a significant value of 0.000 < 0.05 (significance level). Based on the results of the f test (simultaneous) it shows that the Discount Program and Social Proof variables simultaneously have a significant effect on Purchasing Decisions. Where the f count value is 99.190 > 3.09 (f table), with a significant value of 0.000 < 0.05 (significance level).